“Living in a Communal Garden” Associated with Well-Being While Reducing Urban Sprawl by 40%: A Mixed-Methods Cross-Sectional Study - Anderson, Jamie (Frontiers in Public Health, 2015)
Background: The extent to which novel land-efficient neighbourhood design can promote key health behaviours is examined, concentrating on communal outdoor space provision. Objectives: To test whether a neighbourhood (Accordia) with a higher ratio of communal to private outdoor space is associated with higher levels of resident’s a) self-reported local health behaviours and b) observed engagement in local health behaviours, compared to a matched neighbourhood with lower proportion of communal outdoor space provision. Methods: Health behaviours were examined via direct observation and postal survey. Bespoke observation codes and survey items represented key well-being behaviours including: ‘connecting’, ‘keeping active’, ‘taking notice’, ‘keep learning’ and ‘giving’. The questionnaire was validated using psychometric analyses and observed behaviours were mapped in real-time. Results: General pursuit of health behaviours was very similar in both areas but Accordia residents reported substantially greater levels of local activity. Validated testing of survey dataset (n=256) showed support for a stronger Attitude to Neighbourhood Life (connecting and giving locally) in Accordia and partial support of greater physical activity. Analyses of the behaviour observation dataset (n=7,298) support the self-reported findings. Mapped observations revealed a proliferation of activity within Accordia’s innovative outdoor hard spaces. Conclusion: Representation is limited to upper-middle class UK groups. However, Accordia was found to promote health behaviours compared a traditional neighbourhood that demands considerably more land area. The positive role of home zone streets, hard-standing and semi-civic space highlights the principle of quality as well as quantity. The findings should be considered as part of three forthcoming locally-led UK garden cities, to be built before 2020.